1995
DOI: 10.1159/000188479
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Dialysis Membranes on Lipid and Lipoprotein Serum Profiles in Hemodialysis Patients

Abstract: We measured the serum concentrations of a variety of lipid constituents – total cholesterol, triglycerides, high-density lipoprotein (HDL) cholesterol, low-density lipoprotein cholesterol, apolipoproteins A1 and B, and lipoprotein(a) – in well-matched uremic patients undergoing chronic hemodialysis with either cuprophane (n = 13) or polysulfone (n = 13) membranes. We found that the patients on polysulfone membrane dialysis had significantly higher mean HDL cholesterol and apolipoprotein A1 concentrations than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…It has also been demonstrated that the use of high-flux membranes is closely associated with a significant reduction in serum triglyceride levels as well as by an increase in HDL-cholesterol levels. 25,26 This improvement might be attributed to an increase in the apolipoprotein C-II/C-III ratio which increases the activity of lipoprotein lipase and facilitates the intravascular lipolysis of triglyceriderich lipoproteins and the type of dialysate that may significantly affect the serum levels of lipoproteins in this population. 4 Additionally, chronic heparin usage during HD sessions might be another important factor in which heparin releases lipoprotein lipase from the endothelial surface and this may result in defective catabolism of triglyceride-rich lipoproteins via decreasing the serum levels of lipoprotein lipase.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been demonstrated that the use of high-flux membranes is closely associated with a significant reduction in serum triglyceride levels as well as by an increase in HDL-cholesterol levels. 25,26 This improvement might be attributed to an increase in the apolipoprotein C-II/C-III ratio which increases the activity of lipoprotein lipase and facilitates the intravascular lipolysis of triglyceriderich lipoproteins and the type of dialysate that may significantly affect the serum levels of lipoproteins in this population. 4 Additionally, chronic heparin usage during HD sessions might be another important factor in which heparin releases lipoprotein lipase from the endothelial surface and this may result in defective catabolism of triglyceride-rich lipoproteins via decreasing the serum levels of lipoprotein lipase.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it has been shown that the use of high-flux polysulfone or cellulose triacetate membranes instead of low-flux membranes is accompanied by a significant reduction in serum triglyceride levels as well as by an increase in apolipoprotein AI and HDL-cholesterol levels [86, 87]. This improvement could, at least in part, be attributed to an increase in the apolipoprotein C-II/C-III ratio which increases the activity of lipoprotein lipase and facilitates the intravascular lipolysis of triglyceride rich-lipoproteins [88].…”
Section: Lipids In Hemodialysis and Peritoneal Dialysismentioning
confidence: 99%
“…[49]. This disharmony might be attributed to their shorter study duration in comparison to us (3 vs. 9 months) an explanation put forward by Docci and co-workers (1995) who concluded that only long-term dialysis induced the noticed lipid parameters improvements [50].…”
Section: Discussionmentioning
confidence: 62%